1988
DOI: 10.1002/ajmg.1320300114
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary communication: Photoanthropometric analysis of individuals with the fragile X syndrome

Abstract: A photoanthropometric method, which enables an objective description of facial structures, was used to examine 31 boys with the fragile X or Martin-Bell syndrome below the age of 12 years. The age range was 1.5 to 12 years with an average age of 6.5 years. Facial parameters were measured from strict frontal and profile photographs of fra(X) syndrome boys and compared with other facial measurements from the same face (e.g. mouth width vs. bizygomatic diameter). We studied 18 photoanthropometric facial parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The photoanthropometric method used in this study follows the protocol established by Stengel-Rutkowski et al (1984) and utilized by Butler et al (1988) in the study of fragile X syndrome and more recently in Prader-Willi syndrome patients (Butler et al 1995). This methodology enables an objective description of facial structures and allows a comparison of normative standards for age and race.…”
Section: Methodsmentioning
confidence: 99%
“…The photoanthropometric method used in this study follows the protocol established by Stengel-Rutkowski et al (1984) and utilized by Butler et al (1988) in the study of fragile X syndrome and more recently in Prader-Willi syndrome patients (Butler et al 1995). This methodology enables an objective description of facial structures and allows a comparison of normative standards for age and race.…”
Section: Methodsmentioning
confidence: 99%
“…Butler et al (1992) also reported anthropometric standards for clinical use for weight, height, head circumference, ear length and testicular volume for fra(X) syndrome males. Until recently, these were only a few studies reporting on the linear growth patterns in fra(X) syndrome individuals (Partington 1984, Meryash et al 1984, Sutherland & Hecht 1985, Locsch et al 1988, Butler et al 1988a, Butler et al 1988b, Saul 1988. Our current research focuses on the development of anthropometric and craniofacial patterning profiles of mentally retarded males with and without the fra(X) syndrome through a comprehensive assessment of measurements at several body sites.…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…The photoanthropometric method used in this study follows the protocol established by Stengel-Rutkowski et al (6) and utilized by Butler et al (7) in the study of fragile X syndrome and more recently in PWS patients without growth hormone therapy (5). This methodology enables an objective description of facial structures and allows a comparison with normative standards for age and race.…”
Section: Methodsmentioning
confidence: 99%
“…palpebral fissure width and bizygomatic diameter). Sixteen photoanthropometric craniofacial indices were studied following the protocols established by Stengel-Rutkowski et al (6) and Butler et al (7). Several suggestive findings in PWS patients were documented by the photoanthropometric analysis including a narrow palpebral fissure width (particularly in older children 6-12 years of age), a high midface, a broad interalar distance, a short back of nose, a prominent high chin and broad low-set ears.…”
mentioning
confidence: 99%